2018
DOI: 10.1101/468454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reorganization of budding yeast cytoplasm upon energy depletion

Abstract: Yeast cells, when exposed to stress, can enter a protective state in which cell division, growth and metabolism are downregulated. They remain viable in this state until nutrients become available again. How cells enter this protective survival state and what happens at a cellular and subcellular level is largely unknown. In this study, we used electron tomography to investigate the stress-induced ultrastructural changes in the cytoplasm of yeast cells. After ATP depletion, we observed a significant cytosolic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…As a result, stationary cells have more LDs than log-phase dividing cells. A recent report showed that the number of LDs increased even when yeast cells were given a short period of glucose starvation by replacing glucose with a non-hydrolysable glucose analogue [ 46 ]. At stationary phase, fatty acids are released slowly from triglycerides and degraded via β-oxidation, to provide energy necessary for cellular maintenance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, stationary cells have more LDs than log-phase dividing cells. A recent report showed that the number of LDs increased even when yeast cells were given a short period of glucose starvation by replacing glucose with a non-hydrolysable glucose analogue [ 46 ]. At stationary phase, fatty acids are released slowly from triglycerides and degraded via β-oxidation, to provide energy necessary for cellular maintenance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This points to a well conserved mechanism, likely dependent on a concomitantly reduced availability of free GTP (27). Moreover, energy depletion (ED) leads to a general reorganization of the cytoplasm including solidification of the periplasm, general water loss and reduction of the nuclear and cellular volume, which allows cells to endure under unfavorable conditions (28)(29)(30)(31). If the shutdown of active nuclear transport coincides with the alteration in passive diffusion and potentially a conformational adaption of NPC architecture remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the yeast eIF2B forms polymers under conditions of stress in vivo [25][26][27][28]. These latter data raise the possibility that eIF2B may bind nucleotides or sugars that regulate its function.…”
Section: Conservation Of Eif2b and Isrib Pocketmentioning
confidence: 98%